Differentiated learning and mathematical creative thinking: The use of Vos Viewer in literature mapping bibliometric analysis - Nindi Sri Rahayu; Muhamad Sofian Hadi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
The purpose of this study was to analyze publications on differentiated learning and mathematical creative thinking in order to increase aligned referrals. Data collection techniques used PoP (Harzing) software, while data analysis utilized VOS Viewer software. A total of 200 articles on differentiated learning and mathematical creative thinking were retrieved from Google Scholar data sources from 2013 to 2023 and were analyzed using a bibliometric analysis approach. The bibliometric analysis included sources, authors, and accuracy derived from the keywords "differentiated learning and mathematical creative thinking," which were analyzed by the author and illustrated using the VOS Viewer software. Based on the study's results, it was found that there is a relationship between the term "differentiated" and the words "creative thinking, curriculum, teachers, and public junior high schools." Furthermore, the term "differentiated" is widely used in research on "differentiated learning," including differentiation and its relation to creative thinking. This research was widely conducted in 2018-2019. Additionally, many other researchers have carried out research on differentiation in differentiating learning. Future researchers can choose data sources other than Google Scholar in PoP (Harzing) software during data collection to enhance this research in increasing aligned references regarding differentiated learning and mathematical creative thinking.